Detection of Circularly Polarized Luminescence of a Cs-Eu(III) Complex in Raman Optical Activity Experiments - Wu, Tao; Kapitán, Josef; Mašek, Vlastimil; Bouř, Petr (Angewandte Chemie (International ed. in English), 2015)
Circularly polarized luminescence (CPL) spectra are extremely sensitive to molecular structure. However, conventional CPL measurements are difficult and require expensive instrumentation. As an alternative, we explore CPL using Raman scattering and Raman optical activity (ROA) spectroscopy. The cesium tetrakis(3-heptafluoro-butylryl-(+)-camphorato) europium(III) complex was chosen as a model as it is known to exhibit very large CPL dissymmetry ratio. The fluorescent bands could be discriminated from true Raman signals by comparison of spectra acquired with different laser excitation wavelengths. Furthermore, the ROA technique enables fluorescence identification by measuring the degree of circularity. The CPL dissymmetry ratio was measured as the ROA circular intensity difference of 0.71, the largest one ever reported. The alternative CPL measurement enhances applications of lanthanides in analytical chemistry and chemical imaging of biological objects.
Keywords: Raman optical activity; chiral fluorescent chromophores; circularly polarized luminescence; Raman imaging; lanthanides